2023
DOI: 10.1186/s12889-023-16100-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the reciprocal relationship between activities of daily living disability and depressive symptoms among middle-aged and older Chinese people: a four-wave, cross-lagged model

Jiayi Wang,
Nansheng Luo,
Yu Sun
et al.

Abstract: Background Early studies have shown a relationship between activities of daily living (ADL) disability and depressive symptoms in older people. However, discussions on the direction of this relationship are insufficient. The study’s objective was to assess the reciprocal relationship between ADL disability and depressive symptoms among middle-aged and older Chinese people. Method Data was collected in four waves of a nationwide survey, the China He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…We found that depressive symptoms are a key predictor of disability in older adults. This finding is consistent with previous research (44)(45)(46), which demonstrates a longitudinal association between depressive symptoms and disability in older adults. Over time, individuals with higher baseline depression levels are more likely to report difficulties in ADL abilities.…”
Section: Discussionsupporting
confidence: 93%
“…We found that depressive symptoms are a key predictor of disability in older adults. This finding is consistent with previous research (44)(45)(46), which demonstrates a longitudinal association between depressive symptoms and disability in older adults. Over time, individuals with higher baseline depression levels are more likely to report difficulties in ADL abilities.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, early identification and intervention for depressive symptoms, along with the promotion of self-care abilities and ADL functioning, are crucial in this population. In comparison to previous studies [ 57 , 58 ], our findings align with established links between depressive symptoms and ADL disability while shedding further light on the role of ADL disability in sarcopenia development. It is crucial to consider the magnitude of these associations, as they hold clinical significance, underscoring the need for targeted interventions.…”
Section: Discussionsupporting
confidence: 89%
“…There seems to be a bidirectional relationship between disability in ADL and depression in middle-aged and older people [ 22 ]. However, most previous studies have been cross-sectional, making it difficult to determine cause and effect.…”
Section: Introductionmentioning
confidence: 99%